Analisis Stabilitas Lereng pada Longsor Desa Caok, Purworejo, Jawa Tengah - Rokhmat Hidayat (JURNAL SUMBER DAYA AIR, 2018)
Landslide occurred on June, 19th 2016 in Caok Village, Purworejo,Central Java. Caok Village is part of Menoreh hills area. Most of Slope in the landslide location has more than 20o. Before the landslide, rain occurred with maximum intensity 325mm/day. This is an indication that landslide was triggered by groundwater infiltration process, caused by high rainfall intensity and steep slopes. In this research, slope stability analyzed using Plaxis and Geo-slope software. Data that are soil engineering properties, steep slope, and groundwater table modelling with Plaxis and Geo-slope software to obtain slope stability and deformation. Minimum number factor of safety is 1,25 (Bowless 1984), without earthquake. Safety factor 1,162 obtained from Geo-Slope model, while with Plaxis resulted 0,9522 with maximum displacement 205m. Both the results of safety factor indicate that the location of the study are prone to landslide.